CLUSTERING ANALYSIS FOR INTRASPECIFIC VARIATION STUDIES AMONGST THE POPULATIONS OF CIRRHINUS MRIGALA - F. Rasool; N. A. Qureshi; M. Siddique; M. Ashraf; A. Ali; A. Hameed; S. Parveen (Journal of Animal and Plant Sciences, 2013)
The agglomerative clustering analysis to find out the intraspecific variations among the populations of Cirrhinus mrigala was done by using Pearson Correlation Coefficient based Unweighted Pair Group Method with Arithmetic Mean (UPGMA) as Agglomeration method by XLSTAT 2012 version 1.02. The data on morphometrics of the samples of C. mrigala populations were collected from five different geographical sites of the farmed and natural water fish. A dendrogram with the data on the morphometrics of the representative samples of each site divided the populations of C. mrigala in to four major clusters or classes. From the results it is clearly indicated that variance decomposition for the optimal classification values remained as, 27.28% for within class variation while 72.72% for the between class differences. The distance between the class/cluster centroids remained as; 50.820 for class one and two, 18.063 for class one and three, 14.564 for class one and four, 68.856 for class two and three, 36.708 for two and four while this distance between class three and four centroids was 32.408. A measurable distinction between the classes of the populations of the C. mrigala was indicated in this study which determined the impacts of changing environment and other possible factors influencing the intraspecific variation among the populations of the same species.
Keywords: Intraspecific; AHC; Cirrhinus mrigala; Morphometric